Factors influencing cybersecurity performance mediated by cybersecurity readiness in public organizations of UAE - Alshemili, Sulaiman Mohammed Sulaiman Alsagheer (2023)
The increasing digitization of services and operations in the United Arab Emirates (UAE) has necessitated an urgent need to understand the factors that influence cybersecurity readiness and its subsequent impact on cybersecurity performance. As the UAE has become one of the most targeted nations for cybercrime, effective strategies to combat these threats have become critical. Further, based on a preliminary study, it was found that despite the high levels of readiness and performance in certain aspects, there are notable shortcomings, particularly in organizational readiness and the awareness of organizational security. This context, coupled with the findings of the preliminary study highlight the urgent need for a research on cybersecurity readiness in UAE public organizations. This study seeks to identify the key factors that contribute to cybersecurity readiness and how they subsequently affect cybersecurity performance within organizations in the UAE. Specifically, framed by Technology-Organization-Environment (TOE) Framework, this study examined the influence of IT infrastructure, employees’ skills, top management support, government regulations, government support, and industry standards on cybersecurity readiness and performance. Data were collected from 238 employees of the three largest public organizations in Abu Dhabi and analysed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) approach. The findings revealed that IT infrastructure, employees’ skills, top management support, and government regulations significantly influence cybersecurity readiness, which in turn impacts cybersecurity performance. While government support was found to significantly influence organizational cybersecurity performance, it did not significantly influence cybersecurity readiness. Industry standards significantly affected cybersecurity readiness but did not have a significant impact on organizational cybersecurity performance. Cybersecurity readiness was found to mediate the relationships between IT infrastructure, employees' skills, top management support, government regulation, industry standards and cybersecurity performance. However, it did not mediate the relationship between government support and cybersecurity performance. The study highlights the importance of a multifaceted approach towards enhancing cybersecurity readiness and performance in organizations, thereby contributing to a safer and more secure digital environment in the UAE. These findings carry significant implications for policy makers, regulators, and organizational leaders, emphasizing the need for a comprehensive strategy involving robust IT infrastructure, skilled workforce, supportive management, effective regulations, and adherence to industry standards, complemented by a strong focus on enhancing cybersecurity readiness. It paves the way for strategic decision-making and effective interventions that not only maintain but further enhance the country's cybersecurity readiness and performance, thereby strengthening its resilience against an evolving cyber threat landscape.